Fundamentals of physics questions & solutions - Intan Syaffinazzilla Zaine; Noorezal Atfyinna Mohd Napiah; Noor Fadhilah Muhamad Sahapini (Oxford Fajar Sdn. Bhd., 2015)
Questions & Solutions: Fundamentals of Physics 2 is a revision book written in question-and-answer format and is specially tailored for students taking introductory Physics courses in local institutions of higher education. Each chapter in this book is divided into four sections: brief notes, solved questions, solved model examination questions, and exercises for students to attempt on their own. The model solutions serve to develop and sharpen students' answering skills while the exercises provide further practice. Designed as a quick revision tool for smart learning, this is a practical book for revision purposes. Altogether, this book contains more than 300 questions with fully worked solutions.